Tibial Fracture Exacerbates Traumatic Brain Injury Outcomes and Neuroinflammation in a Novel Mouse Model of Multitrauma. Issue 8 (August 2015) - Shultz, Sandy R; Sun, Mujun; Wright, David K; Brady, Rhys D; Liu, Shijie; Beynon, Sinead; Schmidt, Shannon F; Kaye, Andrew H; Hamilton, John A; O'Brien, Terence J; Grills, Brian L; McDonald, Stuart J
Multitrauma is a common medical problem worldwide, and often involves concurrent traumatic brain injury (TBI) and bone fracture. Despite the high incidence of combined TBI and fracture, preclinical TBI research commonly employs independent injury models that fail to incorporate the pathophysiologic interactions occurring in multitrauma. Here, we developed a novel mouse model of multitrauma, and investigated whether bone fracture worsened TBI outcomes. Male mice were assigned into four groups: sham-TBI +sham-fracture (SHAM); sham-TBI+fracture (FX); TBI+sham-fracture (TBI); and TBI+fracture (MULTI). The injury methods included a closed-skull weight-drop TBI model and a closed tibial fracture. After a 35-day recovery, mice underwent behavioral testing and magnetic resonance imaging (MRI). MULTI mice displayed abnormal behaviors in the open-field compared with all other groups. On MRI, MULTI mice had enlarged ventricles and diffusion abnormalities compared with all other groups. These changes occurred in the presence of heightened neuroinflammation in MULTI mice at 24 hours and 35 days after injury, and elevated edema and blood–brain barrier disruption at 24 hours after injury. Together, these findings indicate that tibial fracture worsens TBI outcomes, and that exacerbated neuroinflammation may be an important factor that contributes to these effects, which warrants further investigation.